Matthew's non-messianic mapping of messianic texts: evidences of a broadly eschatological hermeneutic - Henning, Bruce Harold (Biblical interpretation series, 2021)
"Scholars often explain Matthew's practice of applying non-messianic texts to the messiah by postulating a Christological hermeneutic. In Matthew's Non-Messianic Mapping of Messianic texts, Bruce Henning raises the question of how Matthew applies messianic texts to non-messianic figures. This neglected category challenges the popular view by stretching Matthew's paradigm to a broadly eschatological one in which disciples share in the mission of Jesus so as to fulfill Scriptural hopes. Using Cognitive Linguistics, this volume explores four case studies to demonstrate Matthew's non-messianic mapping scheme: the eschatological shepherd, the vineyard care-giver, temple construction imagery, and the Isaian herald. These reveal how Matthew's theology of discipleship as participating in Jesus' own vocation extends even to his hermeneutical paradigm of fulfillment"--